Interplay among IncA and blaKPC-Carrying Plasmids in Citrobacter freundii - Bitar, Ibrahim; Caltagirone, Mariasofia; Villa, Laura; Mattioni Marchetti, Vittoria; Nucleo, Elisabetta; Sarti, Mario; Migliavacca, Roberta; Carattoli, Alessandra (Antimicrobial agents and chemotherapy, 2019)
We report two KPC-producing Citrobacter freundii isolates from unrelated patients. In one case, blaKPC-2 was harbored on a novel variant of a Tn4401 transposon of an IncN plasmid conjugated together with a coresident IncA plasmid, whereas in the other one, blaKPC-3 was on a Tn4401a transposon located on an IncX3-IncA self-conjugative plasmid fusion. The interplay among plasmids carrying blaKPC and the coresident IncA plasmids offers new information on plasmids coresident within clinically relevant enterobacteria.
Keywords: Enterobacteriaceae; plazmidy; Tn4401i; antibakteriální látky; IncN; Citrobacter freundii; Microbial Sensitivity Tests; Plasmids; IncX3; transpozibilní elementy DNA; DNA Transposable Elements; Tn4401a; IncA; Anti-Bacterial Agents; mikrobiální testy citlivosti; KPC